Zinc oxide nanoparticles induce toxicity in CAL 27 oral cancer cell lines by activating PINK1/Parkin-mediated mitophagy - Wang J (Dove Medical Press, 2018)
Jianfeng Wang,1 Shutao Gao,2 Shuyu Wang,3 Zhaonan Xu,3 Limin Wei31Department of Orthodontics, 2Department of Nuclear Medicine, Handan Central Hospital, Handan, China; 3Department of Pediatric Dentistry, School and Hospital of Stomatology, Wenzhou Medical University, Wenzhou, China Background: Tongue squamous cell carcinoma (tongue cancer) is one of the most common malignancies in the oral maxillofacial region. The tumor easily relapses after surgery, and the prognosis remains poor. Recently, zinc oxide nanoparticles (ZnO NPs) were shown to target multiple cancer cell types. In this study, we aimed to elucidate the anticancer effect of ZnO NPs on CAL 27 human tongue cancer cells and identify the role of PINK1/Parkin-mediated mitophagy in this effect.Materials and methods: We analyzed the dose-dependent cytotoxic effects of ZnO NPs on CAL 27 cells. Cells were cultured in media containing 0, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, or 100 µg/mL ZnO NPs for 24 h. We further examined the intracellular reactive oxygen species levels, monodansylcadaverine intensity and mitochondrial membrane potential following the administration of 25 µg/mL ZnO NPs for 4, 8, 12, or 24 h and investigated the role of PINK1/Parkin-mediated mitophagy in ZnO NP-induced toxicity in CAL 27 cells.Results: The viability of CAL 27 cells decreased after treatment with increasing ZnO NP concentrations. The inhibitory concentration 50% of the ZnO NPs was calculated as 25 µg/mL. The ZnO NPs increased the intracellular reactive oxygen species levels and decreased the mitochondrial membrane potential in a time-dependent manner as well as activated the PINK1/Parkin-mediated mitophagy process in CAL 27 cells.Conclusion: Based on our findings, ZnO NPs may possess potential anticancer activity toward tongue cancer cells. Keywords: zinc oxide nanoparticles, mitophagy, tongue cancer; anticancer therapy